ESTIMATION OF THE RADIATION HAZARD TO A SPACECRAFT PASSING THE VAN ALLEN BELTS IN A LOW THRUST TRANSFER - Barbosa, Gerson; Sukhanov, Alexander; Prado, Antonio F. B. A.; Winter, Othon C. [UNESP]; Martins, Juan [UNESP]; Macau, Elbert; Razoumny, Y. N.; Graziani, F.; Guerman, A. D.; Contant, J. M. (Univelt Inc, 2017)
A spacecraft transfer from a low Earth orbit to outside the Earth sphere of influence using solar electric propulsion is considered. The spacecraft crosses the Van Allen belts many times during the transfer, what can damage the onboard electronic equipment. A simple model of the belt is taken: the belt consists of two spherical parts with homogeneous radiation. The radiation accumulated during the spacecraft passage through the belts is estimated for various transfer orbits using the model. This estimate is done for various parking orbits and transfer times.